Clinical consensus on diagnosis and treatment of patients with chronic exertional compartment syndrome of the leg: a delphi analysis - Vogels, S.; Ritchie, E. D.; van der Burg, B. L. S. B. (Sports Medicine, 2022)
Aim: Defining universally accepted guidelines for the diagnosis and treatment of chronic exertional compartment syndrome (CECS) is hampered by the absence of high-quality scientific research. The aim of this Delphi study was to establish consensus on practical issues guiding diagnosis and treatment of CECS of the leg in civilian and military patient populations. Methods: An international expert group was queried using the Delphi technique with a traditional three-round electronic consultation. Results of previous rounds were anonymously disclosed in the questionnaire of rounds 2 and 3, if relevant. Consensus was defined as > 70% positive or negative agreement for a question or statement. Results: The panel consisted of 27 civilian and military healthcare providers. Consensus was reached on five essential key characteristics of lower leg CECS. The panel achieved partial agreement regarding standardization of the diagnostic protocol, including muscle tissue pressure measurements. Consensus was reached on conservative and surgical treatment regimens. However, the experts did not attain consensus on their approach of postoperative rehabilitation and preferred treatment approach of recurrent or residual disease. A summary of best clinical practice for the diagnosis and management of CECS was formulated by experts working in civilian and military healthcare facilities. Conclusion: The Delphi panel reached consensus on key criteria for signs and symptoms of CECS and several aspects for conservative and surgical treatment. The panel did not agree on the role of ICP values in the diagnostic process, postoperative rehabilitation guidelines protocol, or the preferred treatment approach for recurrent or residual disease. These aspects serve as a first attempt to initiate simple guidelines for clinical practice.